Beyond the Market: Designing Nonmarket Accounts for the United States - Abraham, Katharine Gail; Mackie, Christopher D.; National Research Council (U.S.). Committee on National Statistics; National Research Council (U.S.). Division of Behavioral and Social Sciences and Education; National Academies Press (National Academies Press, 2004)
The national income and product accounts that underlie gross domestic product (GDP), together with other key economic data-price and employment statistics- are widely used as indicators of how well the nation is doing. GDP, however, is focused on the production of goods and services sold in markets and reveals relatively little about important production in the home and other areas outside of markets. A set of satellite accounts-in areas such as health, education, volunteer and home production, and environmental improvement or pollution-would contribute to a better understanding of major issues related to economic growth and societal well-being. Beyond the Market: Designing Nonmarket Accounts for the United States hopes to encourage social scientists to make further efforts and contributions in the analysis of nonmarket activities and in corresponding data collection and accounting systems. The book illustrates new data sources and new ideas that have improved the prospects for progress.